A within-person theoretical perspective in sales research: outlining recommendations for adoption and consideration of boundary conditions. Issue 4 (2nd October 2019) - Childs, Dayle R. N.; Lee, Nick; Dewsnap, Belinda; Cadogan, John W.
Abstract: In the sales literature it is standard practice for researchers to collect cross-sectional data from multiple salespeople, and to compare those salespeople on the data obtained. This between-person approach is suitable for research aiming to draw conclusions between salespeople. However, many salesperson processes are dynamic and vary within salespeople over time, requiring datasets with repeated-measures. This article highlights the need to adopt a within-person theoretical perspective in sales research. Critically, the article shows how our present understanding of boundary conditions may change depending on whether a between-person or within-person level of analysis is adopted. Using examples from the sales literature, we show how the practical implications from between-persons research designs do not necessarily generalize to the within-person level. Further, we explain the methodological and analytical considerations that researchers must account for when undertaking within-person research. Furthermore, the article provides decision criteria that help to identify when within-person analysis should be conducted, outlining analysis tools that are capable of correctly estimating within-person effects without bias. Examples of how within-person research can enhance theory within future sales research, and how within-person research may influence management implications are also discussed. Finally, potential remedies to within-person research barriers are given.